Jaminan Hak Pekerja Yang Terkena Pemutusan Hubungan Kerja Dalam Perjanjian Kerja Waktu Tertentu - Siti Mardiyati (Sekolah Tinggi Ilmu Hukum sumpah Pemuda, 2023)
Workers know or understand their rights and obligations, but because of the scarcity of work, they persist and do not dare to sue even though their rights have been violated by the employer. One form of violation is the issue of Termination of Employment, hereinafter referred to as Termination of Employment. However, when viewed from the perspective of workers, the application of a certain time work agreement system is very unfavorable or tends to be detrimental to workers. What are the factors of termination of employment in a work agreement for a certain time. how is the legal guarantee of the rights of workers who are affected by termination of employment in a work agreement for a certain time. Factors in the occurrence of termination of employment in a work agreement for a certain time. Guarantees for the rights of workers who are subject to termination in a work agreement for a certain time, which includes. the guidance and supervision carried out by technical institutions/institutions in a consistent and continuous manner towards the implementation of the provisions of the applicable laws and regulations in the field of manpower. Socialization must be carried out to workers, especially so that they are aware of their rights as workers as regulated by law.